Evaluating elections : a handbook of methods and standards - Alvarez, R. Michael, 1964-; Atkeson, Lonna Rae, 1965-; Hall, Thad E. (Thad Edward), 1968- (Cambridge [England] : Cambridge University Press, 2013)
'This book focuses on how the tools of public management and policy evaluation can be used to give election officials the data they need to improve elections'--
'In competitive and contested democratic elections, insuring integrity is critical.'Evaluating Elections' shows why systematic analysis and reporting of election performance is important and how data-driven performance management can be used by election officials to improve elections. The authors outline how performance management systems can function in elections and their benefits for voters, candidates, and political parties. Journalists, election administrators, and even candidates often ask whether recent elections were run well, whether there were problems in the administration of a particular state's elections, and how well elections were run across the country. The authors explain that such questions are difficult to answer because of the complexity of election administration and because there is currently no standard or accepted framework to assess the general quality of an election'--
Introduction: Performance-based evaluation of election administration -- 1. The electoral ecosystem -- 2. Easily available data for performance evaluation -- 3. Measuring the experiences of voters -- 4. Measuring the performance of poll workers -- 5. Auditing the election ecosystem -- 6. Election observation.
Includes bibliographical references (p. 159-168) and index.
Keywords: Elections -- United States -- Handbooks, manuals, etc; Elections -- Handbooks, manuals, etc